2003
DOI: 10.4039/n02-099
|View full text |Cite
|
Sign up to set email alerts
|

Release of native Trichogramma minutum to control grape berry moth

Abstract: We studied the effects of inundative releases of the egg parasitoid Trichogramma minutum Riley (Hymenoptera: Trichogrammatidae) on economic injury by grape berry moth, Endopiza viteana (Clemens) (Lepidoptera: Tortricidae). Trichogramma minutum originally collected from natural host populations near North East, Pennsylvania, was mass produced in tobacco hornworm hosts and Mediterranean flour moth. We released T. minutum in border rows, where grape berry moth infestation is typically high, of experiment field st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 23 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Several field studies successfully demonstrated that the presence of buckwheat enhanced parasitism in broccoli (Lavandero et al. 2005), vineyards (Nagarkatti et al. 2003; Berndt, Wratten & Scarratt 2006) and an apple orchard (Irvin et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several field studies successfully demonstrated that the presence of buckwheat enhanced parasitism in broccoli (Lavandero et al. 2005), vineyards (Nagarkatti et al. 2003; Berndt, Wratten & Scarratt 2006) and an apple orchard (Irvin et al.…”
Section: Discussionmentioning
confidence: 99%
“…(6) Junta de Andalucı´a, (2004), (7) Kenis and Kloosterman (1999), (8) Lewis et al (1976), (9) Llorens (1990b), (10) Llorens and Garrido (1992), (11) Massa et al (2001), (12) Nagarkatti et al (2003), (13) Neale et al (1995), (14) Oatman and Platner (1985), (15) Pomerinke and Stansly (1998); (16) Prinsloo and Samways (2001), (17) Smith et al (1990), (18) Sta´ry (1975), (19) Sta´ry and Cermelli (1989), (20) Stibick (2003), (21) Stiling (2004), (22) Stinner et al (1974), (23) Stuart and Polavarapua (2000), (24) Thorpe (1931), (25) Twine and Lloyd (1982), 1999), as well as in areas with a similar climate, such as Australia, California, or South Africa (UC, 1991;Smith et al, 1997;Charleston et al, 2003).…”
Section: Main Crops and Target Pests For Biological Controlmentioning
confidence: 97%
“…The main reasons being that the moth eggs are easily mass produced and inexpensive, and the resulting larvae provide an efficient level of biocontrol against other moth pests (e.g., the European corn borer). They were first used in 1980 against GBM eggs (Barnay et al 1999;Reda Abd el Monsef 2004;Hommay et al 2011;Walton et al 2012), the American grape berry moth Endopizza viteana (Nagarkatti et al 2003), and also against the light brown apple moth Epiphyas postvittana in Australian vineyards (Glenn and Hoffmann 1997). Several species of Trichogramma, such as T. brassicae Bezdenko, T. cacoeciae Marchal, T. dendrolimi Matsumura, and T. minutum Riley, have been used with significant but varying pest reduction results.…”
Section: Parasitoidsmentioning
confidence: 99%